THE ROLE OF MULTILINGUALISM IN LANGUAGE LEARNING - Alimova Madinabonu Islomjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Multilingualism is becoming increasingly prevalent in today's society, with many individuals speaking two or more languages. This has led to a growing interest in the role of multilingualism in language learning, and benefits it can bring to learners. The article explores the benefits of being multilingual when learning a new language, including improved cognitive flexibility and enhanced communication skills. Multilingual induviduals have been found to be better at switching between different languages, which can help them to adapt more easily to new linguistic environments.